The association of Chinese and American antenatal care utilization indices with birth outcomes - Zhou, Haibo; Yang, Yi; Chi, Peihan; Cheng, Haoyue; Alifu, Xialidan; Qiu, Yiwen; Huang, Ye; Zhang, Libi; Ainiwan, Diliyaer; Zhuang, Yan; Liu, Hui; Chen, Zhi; et al. (Frontiers in Public Health, 2024)
Objective Few comparisons have been implemented between different prenatal care utilization indices and their effects on adverse outcomes. This study investigated the appropriateness of Chinese antenatal care (ANC) regulations and compared Chinese and American adequacy of prenatal care utilization (APNCU) scores. Methods From 2010 to 2022, the medical records of 60,114 pregnant women were collected from the electronic medical record system (EMRS) in Zhoushan, China. ANC utilization was measured using the APNCU score and five times antenatal care (ANC5). Birth weight outcomes, including small for gestational age (SGA) and large for gestational age (LGA), low birth weight (LBW), macrosomia, birth weight, and preterm birth (PTB), were utilized as outcomes. Multinomial, linear, and logistic regression were used to analyze the association of ANC5 and APNCU with outcomes, respectively. Crossover analysis was implemented to compare the interaction between ANC5 and APNCU on the outcomes. Results Women who received inadequate prenatal care had increased odds for PTB (ANC5: odds ratio (OR) = 1.12, 95% confidence interval (95%CI) = 1.03–1.21; APNCU: OR = 1.18, 95%CI: 1.07–1.29), delivering SGA infants (ANC5: OR = 1.13, 95%CI = 1.07–1.21; APNCU: OR = 1.11, 95%CI = 1.03–1.20). Crossover analysis revealed that inadequate prenatal care in APNCU only was significantly associated with an increased risk of PTB (OR = 1.48, 95%CI: 1.26–1.73). Conclusion Women with inadequate prenatal care in ANC5 or APNCU were more likely to suffer from adverse birth outcomes, including PTB, birth weight loss, SGA, and LBW. It indicated that adequate prenatal care is necessary for pregnant women. However, there were interactions between ANC5 and APNCU on PTB, with inadequate prenatal care use by APNCU showing the highest risk of PTB. This indicates that APNCU would be a better tool for evaluating prenatal care use.